2011
DOI: 10.1111/j.1365-2125.2010.03814.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymorphisms within the methotrexate pathway genes on the toxicity and efficacy of methotrexate in patients with juvenile idiopathic arthritis

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Methotrexate (MTX), which causes adverse effects, such as liver and/or renal dysfunction, is the most common disease‐modifying antirheumatic drug used for the treatment of rheumatoid arthritis and articular‐type juvenile idiopathic arthritis (JIA). • Pharmacogenetic studies analysing the MTX pathway genes would aid in the development of more personalized therapy. • Results regarding the influence of gene polymorphisms on the toxicity and efficacy of MTX are conflicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%
“…No significant associations between genetic variants and outcome were found in two studies in Caucasian RA patients [28,29] or in a Japanese study that included patients with articular-type juvenile idiopathic arthritis [30]. Two recent publications have suggested that the FPGS is involved in the MTX outcome.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of these polymorphisms on the toxicity and efficacy of MTX is conflicting and there are differences between ethnic groups [32,73]. MTX treatment may also be affected by child development, which may be a predictive factor in pediatric rheumatology [74].…”
Section: Pediatric Rheumatologymentioning
confidence: 98%
“…The influence of polymorphisms within the MTX pathway genes on the toxicity and efficacy of therapy in patients with rheumatoid arthritis and JIA has been studied [70]. Several SNP associations (p-value trend ≤ 0.05) [71] in MTX pathway genes (encoding for SLC19A1 and SLC16A7, MTHFR, GGH, ATIC and BCRP/ABCG2) in patients with JIA have been reported [71][72][73][74][75]. In particular, the GGH gene involved in MTX metabolism with a specific genotype (the non-TT genotype at GGH T16C) was found to be associated with a high risk of liver dysfunction (p = 0.028, OR: 6.90, 95% CI: 1.38-34.5) [73].…”
Section: Pediatric Rheumatologymentioning
confidence: 99%